Boosting Carbon Capture in /Coal Plants with Pinch Analysis for Greener Energy - Nnadikwe Johnson; Iheme Chigozie; Momoh abdulazeez adeyem; Stephen Oyelami (Journal Majelis Paspama, 2026)
Boosting carbon capture in coal-fired power plants is crucial for achieving greener energy and mitigating climate change . Pinch analysis, a systematic optimization technique, enhances carbon capture efficiency by minimizing energy consumption and reducing environmental impact. In coal plants, achieving high-purity CO₂ capture is a key objective. Using a 30% MEA (monoethanolamine) solution for carbon capture introduces an initial energy premium of 17.6%. However, applying pinch assessment techniques results in a significant 12.3% reduction in overall energy consumption. This translates to a substantial 50% decrease in energy requirements for carbon capture operations. The implementation of pinch analysis enables coal-fired power plants to achieve an impressive 90% CO₂ capture efficiency, underscoring the potential of this approach to enhance sustainability and cost-effectiveness. By optimizing heat exchange networks and identifying optimal heat transfer points, pinch analysis reduces energy and water consumption in carbon capture processes. This systematic optimization contributes to operational efficiency improvements, paving the way for greener and more sustainable power generation practices. The use of pinch assessment techniques offers a pathway towards cleaner energy production, reduced environmental footprints, and compliance with global climate goals . By strategically matching hot and cold streams, coal plants can minimize resource usage while boosting carbon capture performance.